Observation and measurement of Higgs boson decays to WW∗ with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, OS; Abramowicz, H; Abreu, H; Abreu, R; et al. (American Physical Society, 2015)
We report the observation of Higgs boson decays to WW ∗ based on an excess over background of 6.1 standard deviations in the dilepton final state, where the Standard Model expectation is 5.8 standard deviations. Evidence for the vector-boson fusion (VBF) production process is obtained with a significance of 3.2 standard deviations. The results are obtained from a data sample corresponding to an integrated luminosity of 25 fb -1 from √s = 7 and 8 TeV pp collisions recorded by the ATLAS detector at the LHC. For a Higgs boson mass of 125.36 GeV, the ratio of the measured value to the expected value of the total production cross section times branching fraction is 1.09 +0.16 -0.15 (stat) +0.17 -0.14 (syst). The corresponding ratios for the gluon fusion and vector-boson fusion production mechanisms are 1.02 ± 0.19(stat) +0.22 -0.18 (syst) and 1.27 +0.44 -0.40 (stat) +0.30 -0.21 (syst), respectively. At √s = 8 TeV, the total production cross sections are measured to be σ(gg→H→WW ∗ )=4.6±0.9(stat) +0.8 -0.7 (syst) pb and σ(VBF H → WW ∗ )=0.51 +0.17 -0.15 (stat) +0.13 -0.08 (syst)pb. The fiducial cross section is determined for the gluon-fusion process in exclusive final states with zero or one associated jet.